2022
DOI: 10.3389/fendo.2022.1010924
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-specific phosphodiesterase 8A and 8B isoforms are differentially expressed in human testis and Leydig cell tumor

Abstract: Cyclic adenosine monophosphate/Protein kinase A (cAMP/PKA) signaling pathway is the master regulator of endocrine tissue function. The level, compartmentalization and amplitude of cAMP response are finely regulated by phosphodiesterases (PDEs). PDE8 is responsible of cAMP hydrolysis and its expression has been characterized in all steroidogenic cell types in rodents including adrenal and Leydig cells in rodents however scarce data are currently available in humans. Here we demonstrate that human Leydig cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…PDE3A is expressed in the heart, vascular smooth Few reports characterized PDE2A expression in testis. Microarray data regarding the expression of PDE genes in different human tissues reported a high level of PDE2A in the human testis [64], later confirmed by the QuantiGene Bioplex Assay [65] (Table 2). Positive results were obtained in human ejaculated spermatozoa [66] while low expression levels were detected in murine spermatozoa [31] (Table 1).…”
Section: Pde3mentioning
confidence: 82%
See 4 more Smart Citations
“…PDE3A is expressed in the heart, vascular smooth Few reports characterized PDE2A expression in testis. Microarray data regarding the expression of PDE genes in different human tissues reported a high level of PDE2A in the human testis [64], later confirmed by the QuantiGene Bioplex Assay [65] (Table 2). Positive results were obtained in human ejaculated spermatozoa [66] while low expression levels were detected in murine spermatozoa [31] (Table 1).…”
Section: Pde3mentioning
confidence: 82%
“…A higher frequency of PDE11A sequence variants in patients with large-cell calcifying Sertoli cell tumors was identified, pointing out how PDE11A could be considered a genetic modifying factor for the development of testicular tumors, acting directly on germ cells or indirectly through somatic cells [166]. Recently, we have demonstrated that during Leydig cell neoplastic transformation PDE8B expression levels increased compared to the normal testis, while PDE8A levels were almost comparable between the two sample groups suggesting, for the first time, a potentially pivotal role of PDE8B in LCs dysfunction [65] (Figure 12). functionally inactivating, resulting in reduced PDE activity and increased cAMP levels (Figure 12) [164].…”
Section: Phosphodiesterases In Testicular Cancermentioning
confidence: 86%
See 3 more Smart Citations